Past changes of spring drought in the inner Tianshan Mountains, China, as recorded by tree rings. (28th February 2017) - Zhang, Ruibo; Yuan, Yujiang; Yu, Shulong; Chen, Feng; Zhang, Tongwen
Abstract : Drought is a common natural disaster in arid Central Asia, and the severity and frequency of drought and other hydroclimatic events are critical to the region's ecology and its residents' livelihoods. In particular, water resource management requires reliable knowledge of climatic variability and annual and centennial drought patterns. In this paper, we establish a 587‐year tree ring chronology using 215 Schrenk spruce ( Picea schrenkiana Fisch. et Mey) samples and reconstruct a spring Palmer Drought Severity Index (PDSI) for the inner Tianshan Mountains spanning the 1645–2008 period. The reconstruction explains 40.3% of the variance during the sub‐period for which we also have reliable observational data (1938–2005). Cross‐validation during this common period also supports our reconstruction model. Spatial correlation analyses with gridded PDSI data show that our PDSI reconstruction reveals a strong regional drought signal for the central and western Tianshan Mountains.